Pengaruh Metode Pembelajaran dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Sejarah Siswa - Lukas Nana Rosana (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2014)
Abstrack The objective of this research was to determine effect of learning method and critical thinking ability toward students’ outcome of learning history at Bunda Hati Kudus Senior High School in Jakarta. This research uses experimental method with treatment of level 2 x 2. The target of sampling population is Bunda Hati Kudus Senior High School Jakarta. The eleventh graders of social one are as the treating sample and the eleventh graders of social two are as controlling popullation. This research gives conclusion as follows: (1) students’ outcome of learning history whom given model make a match of cooperative learning method are higher than students’ outcome whom given convensional learning method; (2) there is an interactive effect between learning method and critical thinking ability toward learning history outcome; (3) students’ outcome of learning history who have high critical thinking ability, were given model make a match of cooperative learning method higher than students who were given convensional learning method; (4) students’ outcome of learning history who have low critical thinking ability, were given model make a match of cooperative learning method lower than students who have low critical thinking, were given conventional learning method. Keywords : history learning outcome, learning methods, and critical thinking abilities